Trends of INR and Fecal Excretion of Vitamin K During Cholestasis Reversal: Implications in the Treatment of Neonates with Intestinal Failure Associated Liver Disease - Dao, Duy T. (JPEN J Parenter Enteral Nutr, 2019)
BACKGROUND: Vitamin K is a fat-soluble compound that plays important roles in coagulation. In children with intestinal failure associated liver disease (IFALD), the disrupted enterohepatic circulation can lead to intestinal loss of vitamin K. Fish oil-based lipid emulsion (FOLE) has proven effective in treating IFALD. As biliary excretion is restored during cholestasis reversal, the accelerated vitamin K loss can pose a risk for deficiency. METHODS: Ten neonates with IFALD receiving FOLE monotherapy were prospectively enrolled in the study from 2016 to 2018. In addition to weekly measurements of international normalized ratio (INR) and direct bilirubin (DB), ostomy output was collected for determination of fecal concentrations of phylloquinone (PK) with mass spectrometry. Trends of DB, INR, and fecal PK concentrations were summarized with locally estimated scatterplot smoothing. RESULTS: The median time (interquartile range) from FOLE initiation to cholestasis reversal was 59 (19–78) days. During cholestasis reversal, INR remained relatively unchanged while the mean (95% confidence interval; CI) daily fecal excretion of PK increased from 25.1 (5.0, 158.5) ng at the time of FOLE initiation to 158.5 (31.6, 1000.0) ng at complete reversal. Examination of individual trends in fecal PK excretion and INR also revealed little correlation between the two measurements (r = −0.10; P=0.50). CONCLUSION: Children with IFALD are at risk for vitamin K deficiency during cholestasis reversal. Close monitoring and quantified supplementation of vitamin K may be warranted during this period. However, this should not be guided by INR alone as it is a poor indicator of vitamin K status.